The Impact of FoMO and TikTok Addiction Among Emerging Adults in Indonesia: A Social Psychological Analysis - Tania Angelica Manek; Stefani Virlia (IJIP : Indonesian Journal of Islamic Psychology, 2025)
This study examines the influence of Fear of Missing Out (FoMO) on TikTok addiction among emerging adults (18-25 years) in Indonesia. The research employs a quantitative approach with data collected from 105 participants through online questionnaires. Using the Fear of Missing Out Scale (FoMOS) and TikTok addiction Scale (SMAS), the study finds a significant positive relationship between FoMO and TikTok addiction, with FoMO contributing 70.4% to TikTok addiction variability (R²=0.704, p<.001). Results reveal that 63.81% of participants spend 4-5 hours daily on TikTok, primarily viewing updates (73.3%), with fashion, culinary, and travel content most preferred. The findings suggest that the higher the level of FoMO, the greater the addiction tendency to TikTok. This research addresses a notable gap in understanding how FoMO specifically influences TikTok addiction among emerging adults, providing valuable insights for developing targeted interventions aimed at promoting healthier social media usage patterns in this vulnerable demographic group